Neutralizing Activity of Anti-interferon-γ Autoantibodies in Adult-Onset Immunodeficiency Is Associated With Their Binding Domains - Yasamut, Umpa (Front Immunol, 2019)
Adult-onset immunodeficiency (AOID) with anti-interferon-γ (IFN-γ) autoantibodies (autoAbs) is an emerging immunodeficiency syndrome in Asian countries. The presence of neutralizing anti-IFN-γ autoAbs are significantly associated with severe disseminated opportunistic infections. However, the characteristics of the neutralizing antibodies in patients are poorly defined. To better understand the properties of the anti-IFN-γ autoAbs in patients with opportunistic infections, a simplified competitive-binding ELISA was developed. The domains recognized by anti-IFN-γ autoAbs were assessed based on their competition with commercial neutralizing mouse anti-IFN-γ monoclonal antibodies (mAbs). First, the binding affinity and neutralizing capacity of these mAbs (clones B27, B133.5, and MD-1) were characterized. Kinetic analysis and epitope binning using bio-layer interferometry showed the comparable binding affinity of these mAbs to full-length IFN-γ and to the adjacent binding region. These mAbs did not recognize the synthetic 20-mer peptides and inhibited IFN-γ-mediated functions differently. In a competitive-binding ELISA, the anti-IFN-γ autoAbs in AOID serum blocked B27, B133.5, and MD-1 mAb binding. This evidence suggested that the autoAbs that competed with neutralizing mouse anti-IFN-γ mAbs recognized a discontinuous epitope of homodimeric IFN-γ as these mAbs. The patient autoAbs that recognized the B27 epitope exhibited strong neutralizing activity that was determined by the functional analysis. Our results demonstrated the heterogeneity of the autoAbs against IFN-γ in AOID patients and the different patterns among individuals. These data expand upon the fundamental knowledge of neutralizing anti-IFN-γ autoAbs in AOID patients.